- #1

Dell

- 590

- 0

i used a parallel axis theorem, then to check myself i found i site which had a direct equation for it

http://www.efunda.com/designstandards/beams/SquareTbeam.cfm

what i did

b1=100mm

h1=12mm

b2=12mm

h2=75mm

q=12.643mm(the distance from the joint of the 2 shapes to the centroid of the T)

>> ((b1*h1^3)/12)+((b1*h1)*(q+h1/2)^2)+((b2*h2^3)/12)+((b2*h2)*(h2/2-q)^2)

**1.4094e-006 m**

^{4}using their equation

t=12mm

y=75-12.643=62.357mm

b=100mm

s=12mm

d=87mm

>> (t*y^3+b*(d-y)^3-(b-t)*(d-y-s)^3)/3

**7.6247e-006**m

^{4}

where have i gone wrong here?